I have 2 problem to solve with the Gauss metohd an im a little lost in that. someone help ?
x + 3y - 2z = -5
2x + -y - z - w = -1
3x - 2y +4w = 1
-x + y - 3z - w = -6
5x + y - z =1
2x - y - z = 0
Now subtract twice the first row from the second, and
subtarct three times the first row from the third, and
add the first row to the fourth:
replace row three by row3+row4-row2, and row 4 by 11(2row4+row2)+row3:
Now replace row 4 by 4row4-61row3:
Now you need to check the arithmetic as I'm not too careful about that.
Then solve starting from the last equation and for the
variables, using the values for the variables found at each step to
substitute into the next earlier equation to solve for the next variable.